A Need Analysis for The Development of Multicultural Learning Model Based on Local Wisdom Integrated Gamification : Public Schools and Female Teachers Need More - Yuyun Elizabeth Patras; Rais Hidayat; Yuli Mulyawati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to analyze teacher needs in Indonesia regarding the development of multicultural learning models based on local wisdom and integrated gamification. This research uses a mixed method that begins with a quantitative approach and continues qualitatively. The quantitative process starts with a literature review to synthesize research indicators and research instruments and distribute instruments to 301 teachers as respondents (urban teachers = 42%, rural teachers = 58%). Quantitative data analysis used the Rasch Model. This qualitative approach uses in-depth interviews with teachers and experts to explain quantitative research findings. The results of this study show a high need for teachers at all levels of education to develop a multicultural learning model based on local wisdom integrated gamification. The need is even greater for public schools and female teachers. This research implies that there must be further efforts to develop multicultural learning models so that they can be implemented in various schools.